REDUCING THE PRODUCTION TIME OF INDONESIAN SWEETENED SOY SAUCE WITH FERMENTATION MODIFICATION - Timothy Henri Suryodinoto (International Journal of Science and Engineering)
Indonesian sweet soy sauce commonly produced using two states of fermentation, the solid-state koji fermentation followed by liquid state of moromi fermentation.  Moromi fermentation may take up to 2 months in common soy sauce production. This research explored alternative fermentation techniques to shorten the production time, and thus reducing production cost, without sacrificing the safety aspect and flavor quality of the sweetened soy sauce. Several modification in the fermentation process was applied and the soy sauce produced. Total plate count and coliform enumeration showed that the soy sauce without moromi fermentation did not meet the national standard of total microbial number. The selected soysauce was then further analyzed for its sensorial and nutritional value. Free choice profiling (FCP) resulted that there is no significance different between each modificated samples.  Proximate and amino acid content were also conducted to characterize the nutritional value. The proximate analysis showed  that the selected soy sauce has met the Indonesian National Standard (SNI) and amino acid content showed that the control soy sauce has more value than other sample.  It can be summed up that modification on koji fermentation was not necessary, meanwhile moromi fermentation could be shortened further, due to safety aspect.